Effect of Giving Salam Leaf Water Decoction on Blood Pressure in Pregnant Women with Hypertension in Puskesmas Murung Pudak - Diyah Amelia Ayu K.D; Nila Widya Keswara; Rosyidah Alfitri (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Hypertension in pregnancy is one of the leading causes of maternal and perinatal morbidity and mortality. Risk factors such as parity, age, and level of knowledge of pregnant women can contribute to the incidence of hypertension, including Severe Pre-Eclampsia (PEB). This study aims to analyze the relationship between parity and the incidence of PEB in pregnant women. This study used a quantitative design with a cross-sectional approach. A total of 20 respondents who met the inclusion and exclusion criteria were included in the study. Data were collected through interviews using a questionnaire and blood pressure measurements before and after the intervention. Statistical analysis was performed with the Shapiro-Wilk test for data normality and the Spearman test to measure the relationship between variables. The results showed that all respondents were in the age range of 20-35 years, with a balanced distribution of parity between primigravida and multigravida. The average blood pressure before the intervention was 162.75 mmHg, indicating hypertension, while after the intervention it decreased to 114.55 mmHg. In addition, there was a significant increase in knowledge level after the intervention (p=0.000). Analysis showed that parity had a correlation with the incidence of PEB, where primigravida had a higher tendency to develop hypertension than multigravida. Demographic factors such as education level and occupation also play a role in increasing pregnant women's knowledge and awareness of the risk of PEB. The conclusion of this study is that educational interventions are effective in increasing the knowledge of pregnant women and contributing to lower blood pressure. In addition, parity can be a risk factor in the incidence of PEB so prevention efforts are needed through education and regular pregnancy monitoring.